Chromanone-type compounds from marine sponge-derived Daldinia eschscholtzii KJMT FP 4.1 - Mada Triandala Sibero, Tao Zhou, Yasuhiro Igarashi, Ocky Karna Radjasa, Agus Sabdono, Agus Trianto, Tiara Ulfa Bachtiarini, Muhammad Syaifudien Bahry (Journal of Applied Pharmaceutical Science, 2020)
In our investigation on chemical diversity of secondary metabolites from marine microorganisms, a sponge-derived fungus was found to produce a glycosylated aromatic compound, karimanone (1). The fungal strain was isolated from an Indonesian sponge Xestospongia sp. collected in Karimunjawa National Park, Central Java, Indonesia, and was identified as Daldinia eschscholtzii based on the internal transcribed spacer rRNA gene sequence. Herein, we describe the isolation and characterization of karimanone (1), a new chromanone-type compound, along with three biosynthetically related metabolites 2–4. All compounds were active against a multidrug-resistant strain of Salmonella enterica ser. Typhi with an MIC of 62.5 μg/ml for compound 2 and 125 μg/ml for compounds 1, 3, and 4.
Keywords: Daldinia, chromanone, sponge-associated fungus.